PKM-KELOMPOK TANI ALAM SUBUR DI DESA NDUARIA KECAMATAN KELIMUTU KABUPATEN ENDE NUSA TENGGARA TIMUR - Yustina Puu; Charly Mutiara; Yohanes Pande (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2019)
Partners in this PKM is Alam Subur Farmers in Nduaria Village that has fifteen members. Based on the results of a survey conducted, it is known that the problems faced by partners are lack of counseling and assistance to farmer groups in the use of inputs and fertilizers and pesticides, the price of chemical fertilizers and pesticides is very expensive and very complicated to obtain, farmers do not know how to make organic fertilizers and pesticides that use plants around the farmers' land, farmers do not know how to control pests and diseases in cabbage and mustard plants, the statutes and bylaws of the group are not legally strong, and group management is still weak. The solution provided to overcome the problems of partners is to provide knowledge and skills to farmers in this group about the facilities and infrastructure used in aquaculture activities, the correct use of fertilizers and pesticides in aquaculture activities, making organic fertilizers and vegetable pesticides from plants around farmer's land, control of pests and diseases in cultivated plants and good group management by making a statute and by laws. Output targets to be achieved in PKM activities include a scientific article published through an ISSN journal, an article in print media, a video of PKM activity, and farmers can make organic fertilizer and pesticides from plants around their land. The methods that will be used in achieving the above objectives are counseling and training. The results achieved are 90% of farmers have understood and can make organic fertilizers and pesticides. DOI: https://doi.org/10.26905/abdimas.v4i2.3480